Pembuatan Cairan Desinfektan dalam Peran serta Penanganan Covid-19 Berdasarkan Instruksi Presiden Nomor 4 Tahun 2020 Bersama PCM Kramat Jati dan Pemuda Muhammadiyah DKI Jakarta - Marjan Miharja; Wiend Sakti Myharto; Yastuty Handalya; Emil Salim; Anggoro Hendrawan; Ryan Hidayat; Jean Magtel Pah; Mayang Maharani Yahya B. (Jurnal Nasional Pengabdian Masyarakat, 2020)
The spread of Covid-19 has become one of the people's concerns, starting in the city of Wuhan, China at the end of 2019 when this virus was discovered, the spread of the virus that the antidote has not yet been found is now out of control. More than 200 countries in the world have reported that their people have contracted the Covid-19 virus. Corona Virus Disease 19 has been declared a Global Public Health Emergency by the World Health Organization (WHO) on January 30, 2020. Conditions in Indonesia until Thursday, November 30, 2020, the number of residents who tested positive for Covid-19 reached 538,883 cases, 450,518 people recovered and 16,945 of them died. This figure will continue to increase in line with the opinion of some epidemiologists and statistics that a pandemic outbreak will not end quickly. The purpose of this community service activity is to realize one of the contents of Presidential Instruction Number 4 of 2020, namely "Rrefocussing activities, reallocation of budgets and procurement of goods and services in order to accelerate the handling of Corona Virus Disease 2019 (COVID-19)", namely by making and distributing fluids. Disinfectant that is safe and environmentally friendly and recommended by the BPOM and the World Health Organization (WHO) to help people face the New Normal era. The result of this service activity is a disinfectant liquid that is safe and environmentally friendly and able to anticipate the spread of covid-19 and increase public awareness of the Covid-19 Virus in the face of the New Normal era.